Food poisoning at a Javanese wedding tradition at Wirogunan Building on July 23rd 2017 - Rieski Prihastuti; Meliana Depo; Trisno Agung Wibowo; . Misinem (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
suspected food poisoning outbreak of 5 cases was reported from Mergangsan primary health care to the Yogyakarta Health Office on July 24th 2017. Objective of this study were to ensure food poisoning outbreak and identify source and route of transmission. A total of 166 respondent was included. All of 83 cases got diarrhea. Epidemic curve showed a common source with incubation period 1-23,5 hours and median incubation was 12 hours. Based on its clinical symptoms and incubation period, this outbreak suspected caused by S.aureus contamination. Statistical analysis showed that the greatest attack rate ratio and odds ratio was found in rendang (AR 3,15 and OR 6,6135; 95% CI 2,7812-16,874). Limitation of this study was there were no sample of food/feces/vomit to confirm the agent.